Seeding after ultrasound-guided percutaneous biopsy of liver metastases in patients with colorectal or breast cancer. (3rd May 2016) - Chen, Inna; Lorentzen, Torben; Linnemann, Dorte; Nolsøe, Christian Pállson; Skjoldbye, Bjørn; Jensen, Benny V.; Nielsen, Dorte
Abstract: Background : Neoplasm seeding is a serious complication after liver metastases biopsy. Reported incidences vary between 10% and 19% for colorectal cancer (CRC) and are unknown for breast cancer (BC). The aim of this retrospective study was to determine the frequency of tumor seeding after ultrasound-guided percutaneous biopsy of CRC and BC liver metastases. Material and methods : Unselected liver biopsies performed in the period of 2005–2012 at our institution were extracted from the National Pathology Registry. Medical records including imaging from patients with biopsy-verified BC and CRC liver metastases were retrospectively reviewed. The endpoint was the development of abdominal wall recurrence following liver biopsy. Results : Of total 2981 biopsies we identified 278 patients with CRC and 155 patients with BC biopsy-verified liver metastases. During the median follow-up of 25 months after biopsy (range 3–253 months), no seeding was recorded in patients with BC. Within the median follow-up of 34 months (3–111 months), seeding was registered in 17/278 (6%) of patients with CRC; three patients of 278 (1%) had undoubtedly biopsy-related seeding, which became apparent six, nine, and 26 months after biopsy, respectively; and in nine patients (3%) seeding occurred due to either biopsy or other interventions; and five patients had seeding, which were assessed as a consequence of other invasive procedures than biopsies. The median overall survival of the 17 patients with seeding was 70 months compared to 39 months of patients without seeding. Conclusions : The results showed no seeding in BC patients. Seeding rate after biopsy in CRC patients is not negligible, however, without affecting outcome.